CRITICAL SUCCESS FACTOR ADOPSI TEKNOLOGI INFORMASI DAN KOMUNIKASI PADA LEMBAGA PEMASYARAKATAN: SEBUAH STUDI KASUS - Sulasno, Mitsal Shafiq; Danutirta, Alif Shofa; Fathoni, Achmad Robbi; Qital, Dari Aulia; Effendy, Vina Ardelia (Infotech: Journal of Technology Information, 2024)
The adoption of communication and information technology has a strategic role in realizing the vision and mission of an organization. The adoption of ICT can have a good influence on employee performance.  Correctional service is one of the aspects of life that also requires an improvement in ICT capabilities, one of which is through the adoption of ICT. The Correctional Technical Implementation Unit is required to always develop in order to meet the goals of corrections. Correctional institutions are expected to adopt ICT to improve the performance of officers. Often, the adoption of ICT in Correctional Institutions does not go as expected. In addition, the adoption of ICT also does not last long. The purpose of this study is to determine Critical Success Factors related to technology adoption in Tangerang Class I Correctional Institution. The TOE framework was used in this study because environmental factors were considered to have a great influence on the place of the case study. This study uses a qualitative-quantitative method (mixed method) with interviews, literature studies, and questionnaires as research instruments. The data obtained from the questionnaire was processed using the Analytical Hierarchy Process (AHP). The results of the study show that the three Critical Success Factors that are the main keys to the success of technology adoption in Tangerang Class I Correctional Institution are Government Support, Culture, and Top Management Support.ABSTRAKAdopsi teknologi komunikasi dan informasi memiliki peran yang strategis dalam mewujudkan visi serta misi sebuah organisasi. Adopsi TIK dapat memberikan pengaruh baik terhadap kinerja pegawai.  Pemasyarakatan merupakan salah satu aspek kehidupan yang juga memerlukan peningkatan dalam kapabilitas TIK yang salah satunya melalui adopsi TIK. Unit Pelaksana Teknis Pemasyarakatan dituntut untuk selalu berkembang dalam rangka memenuhi tujuan pemasyarakatan. Lembaga Pemasyarakatan diharapkan dapat melakukan adopsi TIK untuk meningkatkan kinerja petugas. Seringkali, adopsi TIK pada Lembaga Pemasyarakatan tidak berjalan sesuai harapan. Selain itu, adopsi TIK juga tidak bertahan lama. Tujuan penelitian ini adalah untuk menentukan Critical Success Factor terkait adopsi teknologi pada Lembaga Pemasyarakatan Kelas I Tangerang. TOE framework digunakan pada penelitian ini karena faktor environment dianggap memiliki pengaruh yang besar terhadap tempat studi kasus. Penelitian ini menggunakan metode kualitatif-kuantitatif (metode campuran) dengan wawancara, studi literatur, dan kuesioner sebagai instrumen penelitian. Data yang didapatkan dari kuesioner diolah menggunakan Analytical Hierarchy Process (AHP). Hasil penelitian menunjukkan tiga Critical Success Factor yang menjadi kunci utama keberhasilan adopsi teknologi pada Lembaga Pemasyarakatan Kelas I Tangerang adalah Government Support, Culture, dan Top Management Support.